Synthesis of 1-Nonyl-4-[(6-Deoxy-1,2:3,4-Di-O-Isopropylidene-α-D-Galactos- 6-yl)oxymethyl]1H-1,2,3-Triazole Via Click Chemistry - Jwad, Rasha Saad (Al-Nahrain Journal of Science, 2018)
The SN2 reaction of nonyl bromide with sodium azide in DMF afforded Nonyl azide (1).D-galactose has been protected by acetone in acidic medium gave 1,2:3,4-di-O-isopropylidene-α-D-galactose (2). Williamson etherfication of (2) with propargyl bromide and sodium hydroxide yielded 6-O-(2-Propynyl)-1,2:3,4-di-O-isopropylidene-α-D-galactose(3). [2+3] Cycloaddition of (3) to nonyl azide using Click conditions afforded1-Nonyl-4-[(6-deoxy-1,2:3,4-di-O-isopropylidene-α-D-galactose-6-yl)oxymethyl]1H-1,2,3-triazole(4). All prepared compounds have been characterized by FT-IR ,1H NMR and 13CNMR.